Analysis of the external assessment of the scientific-technological competence in 6th grade of Primary Education (2016) - Tobías Martín Páez; Francisco Javier Carrillo Rosúa; José Luis Lupiáñez Gómez; José Miguel Vílchez González (Enseñanza de las Ciencias, 2019)
This article presents a documentary analysis focused on the external tests assessing the scientific and technological competence in the sixth year of Primary Education from three different points of view. Firstly, we pay attention to its adjustment and adaptation to the variables of the reference theoretical frameworks; secondly, we characterize the presence of scientific and technological competence in the tests and, thirdly, we determine the relationships between the variables and the evaluated competence. 169 activities have been analyzed through triangulation among experts. The results show that the adjustment to the theoretical framework is weak and that the applied competence requires scarce interpretation of data and research design. Finally, there is a symmetrical and positive relationship between cognitive demands and competence level.